Outcomes of Gemcitabine, Vinorelbine, and Doxorubicin in Peripheral T-Cell Lymphoma - Tsumura, Aaron; Looi, David; Moskoff, Benjamin N; Tuscano, Joseph M; Esteghamat, Naseem (Archives of Clinical and Medical Case Reports, 2024)
Peripheral T-Cell Lymphoma (PTCL) remains a difficult-to-treat heterogeneous group of Non-Hodgkin Lymphomas. Our current treatment guidelines have been largely based on studies evaluating the treatment of B-cell Lymphomas, in which there were small subsets of T-cell lymphoma patients included. Additionally, there is no clear guideline for sequencing of subsequent salvage regimens. Prior retrospective studies have reported activity with the combination chemotherapy, Gemcitabine, Vinorelbine, and Doxorubicin (GVD) in the treatment of relapsed and refractory PTCL, but these have been international retrospective analyses. Thus, we performed a retrospective analysis within our own institution of the efficacy and safety of GVD in the treatment of relapsed and refractory PTCL. We found an overall response rate of 80%, complete response rate of 50%. Complete response rates were higher in patients receiving GVD as second-line therapy as compared to later lines of therapy. GVD was well tolerated with the most common adverse effects being neutropenia, infection, and peripheral neuropathy. Ultimately, our data supports the use of GVD in relapsed and refractory PTCL, with possible greatest benefit when used as second-line therapy.